2020
DOI: 10.3906/vet-1909-1
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient digestibility, performance, and egg quality traits of quails raised in different stocking densities and ascorbic acid supplementation in a hot, tropical environment

Abstract: Introduction Quails are commonly raised in multitier cages during both growing and laying periods. Providing an optimal stocking density (SD) for quails will yield optimal laying performance [1]. An optimal SD provides adequate ventilation, airflow, as well as space for birds' movement and access to feed and water [2]. Thus, SD is a serious issue in poultry production because it depends on the country and its production system [3]. Researchers are growingly interested in increasing the SD due to its potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
(49 reference statements)
2
9
0
Order By: Relevance
“…The results observed productive performance due to stocking density accordance with previous studies (Ratriyanto et al, 2020;El-Sheikh et al, 2016;El-Trarbany et al, 2015) who found that, high stocking density decrease egg production, egg weight, egg number and egg mass in Japanese quail. Other observations in these birds (Italian quails) demonstrated that, increasing the stocking density from 38 to 47 qualis/m 2 did not affect their egg production, while increasing the stocking density to more than 56 quail/m 2 causes a decrease in their egg production (Faitarone et al, 2005).…”
Section: Results and Disscutionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results observed productive performance due to stocking density accordance with previous studies (Ratriyanto et al, 2020;El-Sheikh et al, 2016;El-Trarbany et al, 2015) who found that, high stocking density decrease egg production, egg weight, egg number and egg mass in Japanese quail. Other observations in these birds (Italian quails) demonstrated that, increasing the stocking density from 38 to 47 qualis/m 2 did not affect their egg production, while increasing the stocking density to more than 56 quail/m 2 causes a decrease in their egg production (Faitarone et al, 2005).…”
Section: Results and Disscutionsupporting
confidence: 90%
“…Contradicting results were obtained by Ratriyanto et al (2020) who stated that, a high stocking density adversely effects egg quality in quail layers, particularly, the egg shell thickness. Likewise, El-Sheikh et al (2016) reported that, quail layers housed at low density laid eggs had higher shell thickness with or without membranes and egg surface area as compared to those at high density.…”
Section: Egg Quality Traitsmentioning
confidence: 98%
“…Similarly, vitamin C can alleviate the harmful effects of stress by reducing the synthesis and secretion of corticosteroids (McDowell, 2000). Ratriyanto et al (2020) stated that the supplementation of 250 mg/kg vitamin C to the diets of quails reared at 40, 45, and 50 quails/m 2 densities prevented the decrease in egg production of quails housed at high stocking density (50 quails/m 2 ). The positive effect of vitamin C supplementation in stress circumstances is due to the insufficient amount of its synthesised form under these conditions; this situation causes protein catabolism and low protein biosynthesis given the increase of cytotoxic free radicals that damage the cell and cell membranes (İpek et al, 2007).…”
Section: Importance Of Vitaminsmentioning
confidence: 99%
“…This result was in line with founded of Fouad et al (2016) that diets containing lactic acid and butyric acid significantly increased eggshell thickness. Ratriyanto et al (2020) also reported that the addition of ascorbic acid in tropical environments in the diet significantly increased quail eggshell thickness.…”
Section: Discussionmentioning
confidence: 92%